2022
DOI: 10.1021/acs.jcim.2c00124
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Based Protein Stability Analysis and Network Modeling of Multiple Conformational States of the SARS-CoV-2 Spike D614G Mutant: Conformational Plasticity and Frustration-Induced Allostery as Energetic Drivers of Highly Transmissible Spike Variants

Abstract: The structural and functional studies of the SARS-CoV-2 spike protein variants revealed an important role of the D614G mutation that is shared across many variants of concern (VOCs), suggesting the effect of this mutation on the enhanced virus infectivity and transmissibility. The recent structural and biophysical studies provided important evidence about multiple conformational substates of the D614G spike protein. The development of a plausible mechanistic model that can explain the experimental observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…These results suggest that structural rigidity is compromised in NUDT15 due to variants that might affect the protein-drug interaction. These destabilizing mutations greatly affect the stability and integrity of the structure that influences the protein function by altering the protein flexibility and binding efficiency [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that structural rigidity is compromised in NUDT15 due to variants that might affect the protein-drug interaction. These destabilizing mutations greatly affect the stability and integrity of the structure that influences the protein function by altering the protein flexibility and binding efficiency [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such tasks particularly highlight the problem of computational cost and conformational sampling in MD simulations [ 125 ]. One of the possible ways to relieve computational costs is to transition from all-atom to coarse-grained models of proteins [ 102 , 114 , 126 ]. Other options are the use of accelerated molecular dynamics methods [ 84 , 127 ] and enhanced sampling techniques [ 84 , 128 , 129 , 130 , 131 ], including machine learning approaches [ 132 , 133 , 134 ].…”
Section: Determination Of Protein Stabilitymentioning
confidence: 99%
“…MD simulations characterized the conformational landscapes of the full-length S protein trimers detailing conformational transitions between functional states and unveiling previously unknown cryptic pockets [ 65 ]. Our studies revealed that the SARS-CoV-2 S protein can function as an allosteric regulatory machinery that can exploit the intrinsic plasticity of functional regions controlled by stable allosteric hotspots to modulate specific regulatory and binding functions [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. A number of computational studies employed atomistic simulations and binding energy analysis to examine the interactions between the S-RBD Omicron and the ACE2 receptor.…”
Section: Introductionmentioning
confidence: 99%